Aerosol Monitoring over Athens Using Satellite and Ground-Based Measurements - D. G. Kaskaoutis; N. Sifakis; A. Retalis; H. D. Kambezidis (Advances in Meteorology)
Satellite data of moderate spatial resolution (MODIS and MERIS) were used to retrieve the aerosol optical depth (AOD) over the urban area of Athens. MODIS products were obtained at a horizontal resolution of 10 by 10 km2 centered over Athens, while the differential textural analysis (DTA) code was applied to MERIS images to retrieve relative-to-reference AOD with a resolution of 260 m by 290 m. The possibility of exploiting the full resolution of MERIS data in retrieving AOD over a grid of a few hundreds metres was thereby investigated for the first time. MERIS-based AOD, centred at 560 nm, showed strong positive correlation to ground-based PM10 data (R2 = 0.85), while MODIS AOD products were in agreement with both MERIS and PM10. Back trajectories were used to study the impact of atmospheric conditions prevailing during the examined days. Days associated with Saharan air masses corresponded to enhanced AOD and predominance of coarse-mode particles. The results suggest that, at least for the case of Athens, AOD retrieved by MERIS images using the DTA code over cloud-free areas can be related to PM10. The accuracy of retrieval mainly depends on the successful selection of the reference satellite data, namely, an image being least contaminated by tropospheric aerosols.